‘Potret Diri’ melalui Semiotika Riffaterre: Puisi Jahwasang Karya Yoon Dongju - Yuniasti, Herlinda (citeus, 2019)
This article discusses the 'Self-portrait' in modern Korean poetry Jahwasang (hangul: 자화상) by Yoon Dongju using the Riffaterre’s semiotic theory. Semiotic theory assumes that literature is a semiotic fact of humanity. Semiotic means that literature is a collection of meaningful sign systems. The purpose of this study is to find the meaning of 'self portrait' written on Jahwasang. The research method of this study is a qualitative method. Based on the analysis, it can be concluded that poem